2022
DOI: 10.1108/intr-03-2021-0179
|View full text |Cite
|
Sign up to set email alerts
|

Home-based workouts in the era of COVID-19 pandemic: the influence of Fitness YouTubers' attributes on intentions to exercise

Abstract: PurposeHome-based workouts via fitness YouTube channels have become more popular during the pandemic era. However, few studies have examined the role of social media personae related to intention to exercise. The purpose of this study was to investigate the structural relationships between fitness YouTuber attributes: perceived physical attractiveness (PPA), perceived social attractiveness (PSA), perceived similarity (PS), parasocial relationships (PSRs), wishful identification (WI), physical outcome expectati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Finally, the authors of this study presented H7, in which they claimed that a positive and significant mediating/indirect relationship exists between peer influence (independent factor) and social media users' anxiety (dependent variable) by dint of social media healthmisinformation seeking behavior which acts as a mediating variable. In previous studies, while examining individuals' online behavior during COVID-19, scholars have identified that individuals frequently share their pessimistic feelings, thoughts and ideas on their social network accounts (Lobato et al, 2020), which may result in misinformed healthcare behaviors and consequences such as fear of multiple organs failure among the peers, followers, friends, colleague and so forth (Kim et al, 2023). Furthermore, the peer influence Healthmisinformation seeking behavior has been highlighted in previous healthcare studies by identifying its importance that more than 60% of American adults seek online health tips and information from their peers, family members and close groups, particularly during a health emergency or serious health issues (Fox and Duggan, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the authors of this study presented H7, in which they claimed that a positive and significant mediating/indirect relationship exists between peer influence (independent factor) and social media users' anxiety (dependent variable) by dint of social media healthmisinformation seeking behavior which acts as a mediating variable. In previous studies, while examining individuals' online behavior during COVID-19, scholars have identified that individuals frequently share their pessimistic feelings, thoughts and ideas on their social network accounts (Lobato et al, 2020), which may result in misinformed healthcare behaviors and consequences such as fear of multiple organs failure among the peers, followers, friends, colleague and so forth (Kim et al, 2023). Furthermore, the peer influence Healthmisinformation seeking behavior has been highlighted in previous healthcare studies by identifying its importance that more than 60% of American adults seek online health tips and information from their peers, family members and close groups, particularly during a health emergency or serious health issues (Fox and Duggan, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Scholars investigated the effects of misinformation on social media during the initial stage of the COVID-19 pandemic. They found that people exposed to online misinformation are more likely to engage in self-reported misinformed behaviors like regularly rinsing their noses with saline and eating more garlic (Kim et al, 2023). However, they are less likely to engage in evidence-based prevention behaviors like staying isolated and maintaining social distancing.…”
Section: Healthmisinformation Seeking Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Ref. [44] reported that the formation of parasocial relationships based on the perceived physical attractiveness, social attractiveness, and similarity of trainers in YouTube home training positively influences the continuous intention to exercise. Further, Ref.…”
Section: The Moderating Effect Of Parasocial Relationshipsmentioning
confidence: 97%
“…Streamer-oriented attributes refer to the personality traits and characteristics of streamers perceived by the audience, such as perceived social attractiveness ( Kim H.-M. et al, 2023 ), perceived similarity ( Kim H.-M. et al, 2023 ) and streamer skills ( Kim and Kim, 2023 ). Technology-oriented attributes refer to the attributes of live-streaming platforms, live-streaming apps and over-the-top (OTT) services, such as ease of use ( Wang et al, 2021 ), viewing quality ( Xu et al, 2023 ) and stream quality ( Qian et al, 2020a ).…”
Section: Literature Reviewmentioning
confidence: 99%